Nursing Education Practice Update 2022: Competency-Based Education in Nursing - Lisa S. Lewis EdD, MSN, RN, CNE; Lisa M. Rebeschi PhD, MSN, RN, CNE; Ellie Hunt DNP, RN-BC, CPHIMS, CNE (SAGE Publishing, 2022)
Introduction Competency-based education (CBE) is increasingly emphasized in nursing. Professional organizations and regulatory bodies are calling for radical transformation in nursing education along with increased emphasis on developing clinical judgment. Methods This practice update article provides a brief history of CBE in a variety of educational settings including health professions education and demonstrates the value of CBE strategies. The article also provides examples of the application of CBE to nursing education. Conclusion CBE offers the opportunity to enhance interprofessional education, increase the use of simulation, and improve clinical judgment in new graduate and advanced practice nurses.